Haploidentical stem cell transplantation vs matched unrelated donor transplantation in adults with hematologic malignancies: a systematic review and meta-analysis. Issue 1 (1st January 2020) - Ma, Liyuan; Han, Xue; Jiang, Suyu; Meng, Qingqi; Zhang, Liubo; Bao, Hongyu
ABSTRACT: Objectives: Haploidentical hematopoietic stem cell transplantation (Haplo-SCT) and matched unrelated donor transplantation (MUD-SCT) are two important options when a matched sibling donor (MSD) is unavailable. Several studies comparing Haplo-SCT and MUD-SCT have reported inconsistent clinical outcomes. Therefore, it is necessary to synthesize the existing evidence regarding outcomes of stem cell transplantations comparing Haplo-SCT with MUD-SCT. Methods: We searched for titles of articles in MEDLINE (PubMed), Cochrane library, EMBASE database that compared transplantation with Haplo-SCT versus MUD-SCT. To compare clinical outcomes between Haplo-SCT and MUD-SCT, we performed a meta-analysis of 17 studies and reported the pooled odd ratios (OR) of 6 endpoints including overall survival (OS), progression free survival (PFS), non-relapse mortality (NRM), relapse rate (RR), acute graft-versus-host disease (aGVHD) and chronic graft- versus-host disease (cGVHD). Results: We found that Haplo-SCT was associated with a comparable OS (pooled OR of 0.99, 95% Confidence Interval (CI) 0.86–1.14), PFS (OR 1.00, 95% CI 0.88–1.15), NRM (OR 0.83, 95% CI 0.65–1.04) and RR (OR 1.08, 95% CI 0.95–1.22) compared to MUD-SCT. We also found a significantly decreased risk of aGVHD (OR 0.74, 95% CI 0.62–0.88) and cGVHD (OR 0.50, 95% CI 0.38–0.66) in Haplo-SCT group. Conclusion: Results of this meta-analysis demonstrates that Haplo-SCT achieves comparable clinical outcomes compared to MUD-SCT in terms of OS, PFS, TRM and RR, but is better than MUD-SCT in terms of decreased aGVHD and cGVHD risk. Haplo-SCT is a valid option for patient needing urgent transplantation.